(4/(5x+2))-(12/(15x+6))=0

Simple and best practice solution for (4/(5x+2))-(12/(15x+6))=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4/(5x+2))-(12/(15x+6))=0 equation:



(4/(5x+2))-(12/(15x+6))=0
Domain of the equation: (5x+2))!=0
x∈R
Domain of the equation: (15x+6))!=0
x∈R
We calculate fractions
(60x+24)/((5x+2))*15x+(-60x-24)/((5x+2))*15x=0
We multiply all the terms by the denominator
(60x+24)+(-60x-24)=0
We get rid of parentheses
60x-60x+24-24=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 0.66666667(x+4)=14 | | z+72=119= | | 9w=4230w= | | (9+x)^3=45 | | 4=(2x-4)/4 | | 3(w-9)=9w+3 | | 4^3x-7=32^2x | | 6x^2+96x+2304=1926 | | f-82/2=6 | | n(3+9)=13+35 | | 44(x-7)=90 | | f/4+11=14 | | 32+66+x=180 | | 18=6−y | | 1/3(15x-12)=x+4 | | 5y+23=10y-17 | | 30+118+x=180 | | 3y+23=6y+4y-17 | | (5x-7)+(x-1)=180 | | 4(3y+10)=6(2y-9) | | 63+72+x=180 | | 0=1024-16x^2 | | 2-7g=9g | | -3+a/4=4 | | 2/(3y+2)=0 | | r+.50r=1650 | | 2(12-x)=-2x-17)-10 | | 38x^2+99x+63=0 | | 7+11x=180 | | 1=1/8x+2/8 | | 8n+1=7n+8 | | 7x/10+2=10 |

Equations solver categories